2021
DOI: 10.1039/d1sc01901e
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on intermetallics towards efficient electrocatalytic water-splitting

Abstract: Intermetallic compounds exhibit attractive electronic, physical, and chemical properties, especially in terms of a high density of active sites and enhanced conductivity, making them an ideal class of materials for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 245 publications
0
71
0
Order By: Relevance
“…First, some compositions with relatively great inherent corrosion resistance in acid media should be favorably selected to synthesize electrocatalysts, such as nitrides, phosphides, alloys, and intermetallics. [28][29][30]214,247,248] Second, the "anti-corrosion coating," which will simultaneously keep or even boost the activity of inner catalytic species in an acid environment can be utilized, for example, carbon-based materials. [188,249,250] Third, for low-conductive neutral electrolytes, the emphasis should be given to the improvement of intrinsic conductivity and increment of electrochemically active sites of the electrocatalysts themselves.…”
Section: Discussionmentioning
confidence: 99%
“…First, some compositions with relatively great inherent corrosion resistance in acid media should be favorably selected to synthesize electrocatalysts, such as nitrides, phosphides, alloys, and intermetallics. [28][29][30]214,247,248] Second, the "anti-corrosion coating," which will simultaneously keep or even boost the activity of inner catalytic species in an acid environment can be utilized, for example, carbon-based materials. [188,249,250] Third, for low-conductive neutral electrolytes, the emphasis should be given to the improvement of intrinsic conductivity and increment of electrochemically active sites of the electrocatalysts themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, intermetallic compounds are an interesting class of compounds for electrocatalytic OER as they possess ordered structures with intermediate bonding nature (between ionic and covalent), which are different than those of the constituent elements. [20,21] Our recent investigations on intermetallic compounds have shown that they transform partially or completely during harsh alkaline OER to electronically similar LOH structures. [17,[22][23][24][25] Nevertheless, these LOH species are structurally and morphologically different and are responsible for varied electrolyte diffusion, electrochemical surface area, and surface versus bulk activity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 71 ] iv) Binding the lean metals with the NNTM to form intermetallics could effectively maintain the high conductivity owing to the orbital hybridization between two metal species, which assures a certain number of electrons located around the Fermi level. [ 96 ] Such a high conductivity promotes the charge transfer during catalysis by accelerating the surface transformation to the NNTM‐based (oxy)hydroxide active phase, as confirmed by the catalytic behavior of FeSn 2 and MnGa 4 . [ 68,207 ] v) Doping of metalloids into NNTM‐based compounds (e.g., oxides) capture electrons from NNTM and transfer them to neighboring anion atoms owing to their moderate electronegativity.…”
Section: Merits Of S‐ P‐ and F‐block Metals In Water Electrolysismentioning
confidence: 98%
“…[85][86][87][88][89][90][91][92][93][94] These electrocatalysts are now commonly viewed as the precatalyst, which holds huge potential as cheap and efficient HER and OER electrocatalysts because of their attractive qualities including the in situ converted porous nanodomains, optimized electronic structure, and highly intrinsic catalytic active sites. Currently, there are three possible models in terms of the phase reconstruction (Figure 3A): [95,96] i) near-surface reconstruction, ii) partial reconstruction (core-shell), and iii) complete reconstruction. Obviously, the phase conversion tendency is gradually strengthened from model (i) to model (iii).…”
Section: Connotation Of Precatalystmentioning
confidence: 99%
See 1 more Smart Citation